2017
DOI: 10.1089/end.2017.0350
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Disease and Kidney Stones: Abdominal Aortic Calcifications Are Associated with Low Urine pH and Hypocitraturia

Abstract: NCCT-based diagnosis of AAC is associated with low urine pH, hypocitraturia, and uric acid stone formation. The presence of AAC could be considered an additional prognosticator for the utility of alkalinization therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 26 publications
1
14
1
Order By: Relevance
“…In a longitudinal epidemiologic study (CARDIA) Reiner and associates [25] found that the kidney stone formers had greater carotid artery wall thickness. Patel and colleagues [26] demonstrated that the presence of abdominal aortic calcification found on CT was associated with uric acid stone formation, low urine pH, and hypocitraturia.…”
Section: Cardiovascular Disease and Urolithiasismentioning
confidence: 99%
“…In a longitudinal epidemiologic study (CARDIA) Reiner and associates [25] found that the kidney stone formers had greater carotid artery wall thickness. Patel and colleagues [26] demonstrated that the presence of abdominal aortic calcification found on CT was associated with uric acid stone formation, low urine pH, and hypocitraturia.…”
Section: Cardiovascular Disease and Urolithiasismentioning
confidence: 99%
“…Furthermore, a positive association between risk factors for coronary artery disease (smoking) was reported (33). Finally, abdominal aortic calcification found on CT have been associated with uric acid stone formation, low urine pH and hypocitraturia (34).…”
Section: Discussionmentioning
confidence: 96%
“…Unlike prior studies, we used a standardized system working with our radiology colleagues to quantify the amount of calcifications at two anatomic sites. The semiautomated system was previously described by Patel et al, 9 who described an association between abdominal aortic calcifications and low urine pH and hypocitraturia. The significant correlation between calcifications and stone disease in this study, along with prior publications, supports a vascular theory of the development of kidney stones.…”
Section: Discussionmentioning
confidence: 99%
“…Noncontrast CT scans were evaluated and semiautomated CT software (Aquarius iNtuition version 4.4.5; TeraRecon, Inc., San Francisco, CA) were utilized to provide an abdominal aorta (AA), pancreas, and splenic artery (SA) calcification Agatston score, as per previously described methods. 9,10 A detection threshold of 130 HU was used on 3 mm slices. The calcification scores were categorized into four groups: none (score 0), mild (>0-100), intermediate (>100-400), and severe (>400).…”
Section: Methodsmentioning
confidence: 99%